Analisis Evaluasi dan Pengukuran Risiko dalam Implementasi Kurikulum Merdeka di RA Arrahmah: Studi Kualitatif - Salma Rahmania; Wahyu Hidayat (IAIN Parepare, 2025)
This study aims to analyze the evaluation of Merdeka Curriculum implementation and measure the risks arising from its application at RA Arrahmah. The study is grounded in the limited number of studies integrating curriculum implementation evaluation with risk measurement in early childhood education settings, even though curriculum transition requires adequate pedagogical readiness, learning resources, and institutional governance. This research employed a qualitative case study design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings show that the implementation of the Merdeka Curriculum at RA Arrahmah has been carried out through initial assessment, learning planning, play-based learning activities, and evaluation of children’s development. This implementation has positively contributed to children’s creativity, independence, and learning engagement. However, the study also identified several major risks, including limited learning media and teaching materials, insufficient teacher readiness in differentiated instruction and authentic assessment, heterogeneity of children’s abilities, and limited physical facilities and pedagogical references. Based on the risk matrix, most risks fall into moderate to high categories, particularly those related to teacher readiness and the availability of learning resources. The study concludes that successful implementation of the Merdeka Curriculum in early childhood education requires systematic evaluation, strengthened teacher capacity, and well-planned institutional risk management.